Entre o corpo do ator/performer e o espaço urbano: um teatro performativo - Guerra, Ariane (2020)
This thesis investigated the performer's body related to the urban space, understanding the environment as a creative interference for the realization of a performative theater. Understanding the performer himself and his body as a direct reflection of the environment he inhabits, the interaction between performer, spectator and environment is considered crucial to the development of a performative theater. It seeks to understand how the environment - in this case, the street - can stimulate possibilities of expression in actions, through the performer`s body, carrying out relationships and considerations, and having in the scenic-performative action Fragmentos de Corpos Urbanos (2016), from Cia. Última Hora, an example in which theory and practice are amalgamated. Conducting empirical and theoretical research, combining practice as research, the intention is to understand the body as a vertex, a relational matrix between performer and urban space, indicating city as a space for the performer to act is co-created and co-created by this at the moment of its action, in a relationship that is fed back by the components in question, and also generating a performative theater. Based on the understanding that the performer is between theater and performance, and analyzing the possible inter-places of this relationship, the concepts of theatricality and performativity are available as potentialities for what is presented as a performative theater. Seeking to weave a more complete panorama of the interaction between the performer's body in relation to the environment, realizing how this body is transformed into new spatialities and temporalities, and how this situation affects not only the body, but also the Other - being this Other the public, the fellow performer and the environment, has in the ideas of Enation, affordances and metaphors the understanding of a embodied cognition, which is understood as primordial for the artistic field. In layers of analysis that consider the performer, the spectator, body and the urban space, intersections and overlaps are obtained that interfere in the performative theater itself and its actions, in the performers body, and in the form of relationship with public and in the environment.